BRAVERY, PERSISTENCE, INTEGRITY, AND VITALITY ON ADVERSITY QUOTIENT: STUDY ON HIGH SCHOOL STUDENTS - Sri Utami; Muhammad Nur Wangid (Jurnal Eduscience, 2025)
Purpose – This study aims to describe and investigate the influence of bravery, persistence, integrity, vitality, and adversity quotient in adolescent high school students in Tarakan City.